Personaliti dan nilai peribadi asas Pegawai Tadbir Diplomatik dalam era transformasi sektor awam - Fatimah Wati Halim,; Muhammad Zahir Mazlan,; Fatimah Omar, (Penerbit Universiti Kebangsaan Malaysia, 2015)
The main foundation in the strategic transformational framework of Malaysian Public Services 2009-2015 is to make certain more transformational leaders were born and having noble values and integrity. Dilpomatic Officer (PTD) are among the higher leaders in public services responsible for making sure that the strategies were successfully implemented. The question here is do the PTD sucessfully strengthen their personality and personal value matched with the strategic transformation foundation of the public sector. Using the Big Five Personality Model and the basic personal values of the public sector, the aim of this research is to identify the persoanlity factors and basic personal values of PTD after going through the transformation since 2009. The personality measurement IPIP by Goldberg was used to measure the five personality factors. The basic personal values questionnaire was developed by the researchers. Two hunderd sixty five PTD were chosen as respondents using purposive sampling. Data collected were then analyzed using CFA and SEM with the SPSS.15 and AMOS 5.0. Findings showed that the PTDs have matched personality factors and basic personal values with strategic foundation transformation demand that is transformational leadership and having noble values and integrity. The personality factors conscientiousness, openess and not easily agreeable influence 34% of the variance for basic personal values. The findings confirmed that the factor personality and basic personal values need to be paid attention in the development of PTD so that the transformational leadership can be sustained.